Pengaruh kadar air terhadap sifat fisik gula semut melalui analisis regresi linier - Hary Kurniawan; Rucitra Widyasari; Yeni Sulastri (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Granulated palm sugar is a natural sweetener that is increasingly valued for its distinctive flavor, practical granular form, and relatively long shelf life. Its physical quality, however, is highly sensitive to moisture content because the product is hygroscopic and readily absorbs water from the surrounding environment during storage and handling. Changes in moisture content can affect important physical attributes, including density, flowability, and color, which in turn influence product stability, handling performance, and consumer acceptability. This study aimed to evaluate the effect of moisture content on the physical properties of granulated palm sugar using linear regression analysis. Samples were adjusted to five moisture content levels, namely 2.06%, 3.87%, 5.42%, 5.98%, and 7.15% (wet basis), and arranged in a completely randomized design with three replications. The parameters observed were bulk density, tapped density, and color attributes (L*, a*, and b*), which were further used to determine Carr Index (CI), Hausner Ratio (HR), hue angle, and total color difference (ΔE). The results showed that increasing moisture content caused bulk density to decrease, while tapped density, CI, and HR increased, indicating reduced flowability and greater cohesiveness at higher moisture levels. Based on HR classification, granulated palm sugar exhibited low cohesiveness at 2.06% moisture content and shifted to intermediate to high cohesiveness as moisture content increased. Color analysis showed that the product remained within hue angle quadrant I, indicating a brownish-yellow appearance. A high coefficient of determination (R² = 0.9843) also confirmed a strong relationship between moisture content and color parameters. Overall, the findings highlight that moisture control is essential for maintaining the physical quality and handling characteristics of granulated palm sugar during storage and distribution.